Variation in the risk of venous thromboembolism in people with colorectal cancer: a population-based cohort study from England - Walker, A.J.; West, Joe; Card, Timothy R.; Humes, David; Grainge, Matthew J. (Wiley, 2014)
BACKGROUND: Patients with colorectal cancer are at high risk of developing venous thromboembolism (VTE), and recent international guidelines have advised extended prophylaxis for some of these patients following surgery or during chemotherapy. However, our understanding of which patients are at increased risk, and to what extent, is limited.